2007
DOI: 10.1097/mlg.0b013e31804f54bd
|View full text |Cite
|
Sign up to set email alerts
|

Does Suture Material and Technique Really Matter? Lessons Learned From 800 Consecutive Blepharoplasties

Abstract: Blepharoplasty is a safe and effective procedure that can be performed successfully with several established techniques. In our experience, closure with two interrupted 6-0 Prolene sutures and a running 6-0 fast-absorbing gut resulted in the lowest rates of complications and revisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Joshi et al reported in a 3-step grading system a series of procedures with 72% of 568 patients highly satisfied with their results, 21% satisfied, and 5% were unsatisfied. 10 Kim used a 4-step grading system. Of 681 patients, 70% graded their aesthetic result as excellent, 19.4% graded as good, no change in 1.2%, and 9.4% showed a poor result.…”
Section: Discussion Of the Results Of The Standardized Questionnairementioning
confidence: 99%
“…Joshi et al reported in a 3-step grading system a series of procedures with 72% of 568 patients highly satisfied with their results, 21% satisfied, and 5% were unsatisfied. 10 Kim used a 4-step grading system. Of 681 patients, 70% graded their aesthetic result as excellent, 19.4% graded as good, no change in 1.2%, and 9.4% showed a poor result.…”
Section: Discussion Of the Results Of The Standardized Questionnairementioning
confidence: 99%
“…[41] They found significant differences between suture materials and techniques and concluded that a fast-absorbing gut suture along with two interrupted Prolene sutures had the lowest rates of complications and the best cosmetic results [Table 7]. [41]…”
Section: Discussionmentioning
confidence: 99%
“…As there are many methods for blepharoplasty incision closure and many different suture materials [2], in our study we are trying a new method of wound closure strips with deep dermal absorbable sutures and discuss about its advantages and disadvantages. One similar study done earlier showed that that the wound closure strips (Steri-Strip™) brand of co-aptive method (film) was an appropriate option to sutures without rate of wound contamination, dehiscence or skin irritation [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the procedure could have further complications like, keratopathy, lagophthalmos, xerophthalmia, chemosis, ptosis as well as ectropion. Collectively, the commonest complications following blepharoplasty could involve scarring, lagophthalmos and ptosis of the eyelid [2].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%